Requirements engineering : foundation for software quality : 23rd International Working Conference, REFSQ 2017, Essen, Germany, February 27-March 2, 2017, Proceedings /: foundation for software quality : 23rd International Working Conference, REFSQ 2017, Essen, Germany, February 27-March 2, 2017, Proceedings. (2017) - Unknown
No abstract available